Variety in Retailing - Baumol, William J.; Ide, Edward A. (Management Science, 1956)
Many marketing problems which promise to be amenable to the techniques of operations research have apparently not been subjected to systematic analysis. This article is a first attempt at an analysis of one such area—the number of items stocked by a retailer and its relation to his sales, his costs, and his profits.